Pengaruh Model Poject Based Learning Berbantuan Media Pop Up Book terhadap Hasil Belajar Siswa pada Pembelajaran IPAS Kelas IV - Yennita, Yennita; Firman, Firman; Desyandri, Desyandri (Darul Yasin Al Sys, 2025)
This research was motivated by the low learning outcomes of students at school. This research aims to determine the effect of the project based learning model assisted by pop up book media on student learning outcomes in class IV science learning at SD Negeri 33 Sawahan Padang Timur. This type of research is experimental research. The population of this study was all students in class IV-C and IV-D at SDN 33 Sawahan Padang Timur for the 2023/2024 academic year with a total of 55 students. Samples were taken by random sampling, students were obtained from class IV-C as the experimental class and class IV-D as the control class. Data collection techniques use tests. The research results showed that the average learning outcome after being given treatment in the experimental class was 83.19 and the average for control class students was 76.64. hypothesis testing shows and. Because it is 1.961 < 2.013, the hypothesis H0 is accepted and H1 is rejected. Thus, it can be concluded that the project based learning model assisted by pop up book media has no effect on student learning outcomes in class IV science and science learning at SD Negeri 33 Sawahan Padang Timur.